Ouvrières au travail, travaux de femmes. Nantes, XVIIIe-XIXe siècles - Samuel Guicheteau (Les Cahiers de Framespa)
Although it does not bring about a dramatic deskilling of the workforce, industrialisation gradually changes working practices as a whole: it affects all sectors of activities – centralized as well as dispersed – and all workers – men and women, more or less skilled. Employers’ demands to rationalize conflict with workers’ autonomy. They still try to defend their identity, built on work and based on skills and autonomy. Even though this identity is shared beyond gender and skill differences by most workers, it does not give birth to a collective conscience. On the contrary, workers develop a feeling of loyalty to their profession and the most skilled might even look down on the less skilled among them. Therefore, changes in women’s work in Nantes in the eighteenth and nineteenth centuries are related not only to economic transformations but also to the experience made by the various actors : employers may entrust them with tasks requiring little or no skills at all and workers may fight their competition. Women’s work is thus downgraded. Gender differentiation and industrialisation operate in a complex manner especially since workers’ identity is growing more and more masculine along with the workers’ organisations, contributing thus in consolidating this identity and in the making of the original French path to industrialisation.